Can personal hygiene act as a proxy indicator of morbidity profile? A study on orphans of Uttarakhand region - Ahlawat, Parul; Vyas, Shaili; Sharma, Neha; Srivastava, Abhay; Srivastava, Ashok; Semwal, Jayanti (International Journal Of Community Medicine And Public Health, 2019)
Background: A healthy childhood is essential for future growth and development. It is greatly influenced by parent, family, society and environment which formulate attitude, behavior, manner and emotions. Millions of children across the world are deprived of this crucial phase of life; those are the orphans and abandoned children. Methods: This institution-based cross sectional study was carried out with the help of pre-designed semi-structured questionnaire amongst 193 orphans aged 5-14 years to assess the personal hygienic practices and morbidities among orphans and to find out the association between the morbidity with personal hygiene and other risk factors. Results: The leading morbidities observed were poor oral hygiene (57.51%) as a morbidity followed by dental caries (50.58%) and pallor (30.57%). The average morbidity per child was found to be 2. There was significant association between ages, education, personal hygienic practices with the presence of morbidity in the orphans. Conclusions: Practices related to personal hygiene was not satisfactory. There was a significant association between morbidity and personal hygiene. Despite of the fact that these children are highly vulnerable; their health needs are poorly understood and ill served.